2019
DOI: 10.1002/eap.2003
|View full text |Cite
|
Sign up to set email alerts
|

Predicting impact of a biocontrol agent: integrating distribution modeling with climate‐dependent vital rates

Abstract: Species distribution models can predict the suitable climatic range of a potential biological control agent (BCA), but they provide little information on the BCA's potential impact. To predict high population buildup, a prerequisite of biocontrol impact, studies are needed that assess the effect of environmental factors on vital rates of a BCA across the environmental gradient of the BCA's suitable habitats, especially for the region where the BCA is considered for field release. We extended a published specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 75 publications
0
24
0
Order By: Relevance
“…Moreover, combining SDM and mechanistic (process-based) models by integrating physiological models of insect development into SDMs based on habitat suitability may enable more robust predictions of both range shifts [41] and population abundances [42,43]. Using such a combined approach, Augustinus et al [44] identified the climatic factors limiting the population build-up of Ophraella communa Lesage (Coleoptera: Chrysomelidae), a biocontrol candidate of invasive A. artemisiifolia, and predicted its potential population density across its suitable European range and the relative importance of those climatic factors on population growth. Population dynamics models are also commonly used to explore and predict changes in population densities over time, such as Integral Projection Models (IPMs) [45] and DYMEX (Hearne Scientific Software) [46].…”
Section: Weed Biocontrol Efficiency Under Climate Change Ecological Cmentioning
confidence: 99%
“…Moreover, combining SDM and mechanistic (process-based) models by integrating physiological models of insect development into SDMs based on habitat suitability may enable more robust predictions of both range shifts [41] and population abundances [42,43]. Using such a combined approach, Augustinus et al [44] identified the climatic factors limiting the population build-up of Ophraella communa Lesage (Coleoptera: Chrysomelidae), a biocontrol candidate of invasive A. artemisiifolia, and predicted its potential population density across its suitable European range and the relative importance of those climatic factors on population growth. Population dynamics models are also commonly used to explore and predict changes in population densities over time, such as Integral Projection Models (IPMs) [45] and DYMEX (Hearne Scientific Software) [46].…”
Section: Weed Biocontrol Efficiency Under Climate Change Ecological Cmentioning
confidence: 99%
“…Moreover, seven traits were only significantly affected by Ophraella genotype including L1 and L3 survival, adult emergence, developmental time and relative water content of adults. Previous studies on Ophraella showed that a higher survival and faster developmental time would result in a higher population increase and more efficient control of Ambrosia (Augustinus et al 2020). Furthermore, larger body size in insects is generally linked to greater fecundity and access to mates (Blanckenhorn 2000) and is thus expected to further enhance population build-up and expansion in O. communa (Chen et al 2014).…”
Section: Ambrosia-ophraella Genotype Interactionsmentioning
confidence: 99%
“…Insect performance or plant resistance is often tested by analyzing developmental time, weight, survival (Liu et al 2012) and herbivore damage (Stenberg and Muola 2017). These vital rates are important for a BCA's population density, and ultimately impact on the target plant invader (Augustinus et al 2020). For instance, faster developmental time allows more generations per year and a higher survival rate would directly result in higher population growth (Augustinus et al 2020), thus both will contribute to increased feeding damage and, together with leaf area removed (O'Neal et al 2002;Siemann and Rogers 2003) to increased biocontrol efficacy (Gassmann 1996;Lommen et al 2017b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if rising temperatures leads to reduced relative humidity, climate change may also have a negative effect on population build-up of O. communa. Laboratory studies revealed that relative humidity of less than 50% during the warmest time of the day significantly reduced egg hatching rates of this biological control agent (Augustinus and Sun et al 2020). Since biocontrol agent impact is dependent on high population densities (Myers andSarfraz 2017, McEvoy 2018), both temperature and humidity should be considered for models predicting O. communa impact on A. artemisiifolia (Augustinus and Sun et al 2020).…”
Section: Effect Of In-season O Communa Abundance and Damage On A Armentioning
confidence: 99%